2016
DOI: 10.1063/1.4942672
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular magnetization reversal in Pt/[Co/Ni]3/Al multilayers via the spin Hall effect of Pt

Abstract: We experimentally investigate the current-induced magnetization reversal in Pt/[Co/Ni]3/Al multilayers combining the anomalous Hall effect and magneto-optical Kerr effect techniques in crossbar geometry. The magnetization reversal occurs through nucleation and propagation of a domain of opposite polarity for a current density of the order of 0.3 TA/m 2 . In these experiments we demonstrate a full control of each stage: i)the Ørsted field controls the domain nucleation and ii) domain-wall propagation occurs by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…Recently, it has been experimentally observed that an in-plane field can result in asymmetric domain expansion in HM/FM structures [12,[23][24][25][43][44][45]. Here we propose a switching model to explain the AMS directly arising from the asymmetric domain expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been experimentally observed that an in-plane field can result in asymmetric domain expansion in HM/FM structures [12,[23][24][25][43][44][45]. Here we propose a switching model to explain the AMS directly arising from the asymmetric domain expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore σ and the switching directions in Pt/ferromagnet (Pt/FM) and Ta/FM structures are opposite [2][3][4]8,10,[12][13][14][15][16][17]. So far all reported SOT switchings are the SOT switchings of a single ferromagnet [2][3][4]12,14,18,[23][24][25]27], in which reversing either current or in-plane field is necessary to switch magnetization [2][3][4]12,14,18,[23][24][25]27] and the switching rule shown in Figs. 1(a) and 1(b) is well obeyed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have confirmed that such a surface state is intact in Bi 2 Se 3 covered with Fe (Honolka et al, 2012;Scholz et al, 2012) or Co (Ye et al, 2012) with in-plane magnetic anisotropy. Spin-charge coupling effects have been reported by spin pumping (Deorani et al, 2014;Jamali et al, 2015;Kondou et al, 2015;Rojas-Sánchez et al, 2016;Shiomi et al, 2014) and magnetoresistance measurements (Ando, 2014;Li et al, 2014;Yasuda et al, 2016).…”
Section: Ferromagnet/topological Insulator Layersmentioning
confidence: 99%
“…Conventional spin transfer torque (STT) utilizes the spin polarized current to transfer angular momentum from one FM to another FM [5,6], and it has been applied to various spintronic devices such as a magnetic random access memory (MRAM) [7][8][9] and race-track domain wall memory [10]. Recently emerging spin-orbit torque (SOT) opens a new prospect in the magnetization manipulation of the HM=FM bilayers [1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In a SOT device, the electrons flowing in a HM layer with strong spin-orbit coupling are spin polarized and the subsequent spin current transfers its angular momentum to the adjacent FM.…”
mentioning
confidence: 99%